2008
DOI: 10.1210/en.2008-0775
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of TNFα Converting Enzyme (TACE/ADAM17) Causes a Lean, Hypermetabolic Phenotype in Mice

Abstract: Energy homeostasis involves central nervous system integration of afferent inputs that coordinately regulate food intake and energy expenditure. Here, we report that adult homozygous TNFalpha converting enzyme (TACE)-deficient mice exhibit one of the most dramatic examples of hypermetabolism yet reported in a rodent system. Because this effect is not matched by increased food intake, mice lacking TACE exhibit a lean phenotype. In the hypothalamus of these mice, neurons in the arcuate nucleus exhibit intact res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 83 publications
3
71
0
1
Order By: Relevance
“…Since myostatin-deficient mice did not exhibit hyperphagia characteristic of WT animals with reduced leptin levels (9,26), as well as some hypermetabolic mouse models (1, 9), we hypothesized that sensitivity to leptin in these animals is increased such that relatively low leptin levels provide a leptin signal to the brain of sufficient magnitude to maintain food intake at levels similar to that of normal animals with higher leptin levels. Our finding that the ability of exogenous leptin to reduce body weight and food intake is increased in mice lacking myostatin provides direct evidence in support of this hypothesis, although additional work is needed to determine the relative loss of muscle and fat mass induced by leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Since myostatin-deficient mice did not exhibit hyperphagia characteristic of WT animals with reduced leptin levels (9,26), as well as some hypermetabolic mouse models (1, 9), we hypothesized that sensitivity to leptin in these animals is increased such that relatively low leptin levels provide a leptin signal to the brain of sufficient magnitude to maintain food intake at levels similar to that of normal animals with higher leptin levels. Our finding that the ability of exogenous leptin to reduce body weight and food intake is increased in mice lacking myostatin provides direct evidence in support of this hypothesis, although additional work is needed to determine the relative loss of muscle and fat mass induced by leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Gelling et al also reported a relatively small population of mice lacking functional Tace (Tace ∆Zn/∆Zn ) that survive to adulthood and display markedly increased energy expenditure and a lean phenotype. 11 The target molecules responsible for these phenotypes observed in mice with Tace inactivation remain elusive. Because neither TNF-α nor TNF-α receptors-deficient (p55 -/-p75 -/-) mice exhibit a lean phenotype under HFD feeding, 28 it is probable that the participation of TNF-α-TNF-α receptor signaling pathways might be minimal under the current settings.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, previous study using Tace ∆Zn/∆Zn showed alterations in white adipose tissue phenotype displaying features characteristic of brown adipose tissue. 11 Perturbations in sympathetic nervous system outflow to brown adipose tissue might contribute to the hypermetabolic phenotype. However, our mice exhibited no adipose tissue phenotype characteristic of brown adipose tissue, such as increased cellularity and adipocytes with multilocular appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De même, un inhibiteur synthétique d'ADAM17 administré chez des rats hypertendus et insulinorésistants, nourris avec du fructose, mais non obèses, améliore la sensibilité à l'insuline [39]. Les souris déficientes en ADAM17 décrites ci-dessus [19] présentent un phénotype maigre associé à une forte dépense calorique [40]. Une fonction hypothalamique d'ADAM17 contrôlant la balance énergéti-que est évoquée dans ce travail.…”
Section: Revuesunclassified